Chondrocalcinosis and medial unicompartmental knee arthroplasty - Woods, D; Wallace, D; Woods, C; McLardy-Smith, P; Carr, A; Murray, D; Martin, J; Gunther, T (1995)
The presence of chondrocalcinosis in a knee which otherwise fulfils the criteria for unicompartmental knee arthroplasty has been considered a contraindication to this procedure. This paper compares the results of two groups of patients undergoing unicompartmental knee arthroplasty; there were 78 knees with degenerative arthritis, and 20 knees with degenerative arthritis and chondrocalcinosis, as proven histologically. The survival rates were not significantly different as determined by the log rank test. There was no significant difference between the groups using pain scores as an outcome measure, nor radiologically. We believe that chrondocalcinosis is not a contraindication to unicompartmental knee arthroplasty. © 1995.